ANALISIS TEGANGAN PADA BEJANA TEKAN VERTIKAL 13ZL100040291 DI PT. ANEKA GAS INDUSTRI - Efrando Manullang; Stenly Tangkuman; Benny Maluegha (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2016)
ABSTRACT A pressure vessel is a container for a pressurized fluid, both liquid or gas. The stress on the shell of pressure vessel must have serious attention because the stress is the basic in determining the dimension and the type of material used, and also the treatment for the pressure vessel. This research intended to obtain the maximum stress in the pressure vessel 13ZL100040291 of the working pressure. The object of this research was a vertical type cryogenic pressure vessel at PT. Aneka Gas Industri, sagrat, Bitung. The analysis was conducted by applying the finite element method aided by softwares. Research results showed that the maximum stress at the inner vessel based on the software simulation is 203,79 MPa, with nominal stress of 33.965 MPa. The nominal stress based on the calculation using mechanical theory is 37,24 MPa. The stress calculation in simulation using software had considered the stress concentration. Afterwards, based on the simulation results, it was found that the stress concentration at the inner vessel and outer vessel is 6. The maximum stress calculated by the simulation software at inner vessel and outer vessel is stell in the safe limit, because the Von Mises stress is smaller than the allowed stress of each material used. Keyword: pressure vessel, inner vessel, outer vessel, stress